The Condom Kingdom - Anirvina, C. (Indian Journal of Marketing, 2009)
With a billion plus population and appalling illiteracy levels in India, can there be any better device than condoms for the government to enforce the small family norm? In fact, it helps to kill two birds with one stone, that is, both family planning and the controlling of sexually transmitted diseases. Demographic explosion poses a major challenge to India’s rapid economic development. The realization on the fallouts of rampant growth in population prompted the government to initiate a simple, non-clinical family planning programme. On the other hand-equally important-condom manufacturers are beginning to appreciate that in a frankly competitive market, future sales depend on new, more candid, consumer- centered approach. Paradoxically, India, a country which is craving for women’s liberalization, needs to pay new attention to the role of men as the responsible parent.